The U.S.-China Military Scorecard Forces, Geography, and the Evolving Balance of Power, 1996-2017 - Heginbotham, Eric (RAND Corporation, 2015)
A RAND study analyzed Chinese and U.S. military capabilities in two scenarios (Taiwan and the Spratly Islands) from 1996 to 2017, finding that trends in most, but not all, areas run strongly against the United States. While U.S. aggregate power remains greater than China's, distance and geography affect outcomes. China is capable of challenging U.S. military dominance on its immediate periphery-and its reach is likely to grow in the years ahead.